2018
DOI: 10.1002/jcb.27581
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles‐mediated communication between endothelial cells modulates, endothelial survival, and angiogenic function via transferring of miR‐125a‐5p

Abstract: Endothelial cells (ECs) released microvesicles (EMVs) could modulate the functions of target cells by transferring their microRNAs (miRs). We have reported that miR-125a-5p protected EC function. In this study, we determined whether EMVs provided beneficial effects on ECs by transferring miR-125a-5p. Human brain microvessel ECs were transfected with miR-125a-5p mimic or miR-125a-5p short hairpin RNA to obtain miR-125a-5p overexpressing ECs and miR-125a-5p knockdown ECs, and their derived EMVs. For the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…The number and size of MSC-EXs were detected by the NanoSight NS300 instrument as we previously described [21, 24]. In this study, diluted suspensions containing MSC-EXs were loaded into the sample chamber and the camera level was maintained at 9 for light scatter mode.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number and size of MSC-EXs were detected by the NanoSight NS300 instrument as we previously described [21, 24]. In this study, diluted suspensions containing MSC-EXs were loaded into the sample chamber and the camera level was maintained at 9 for light scatter mode.…”
Section: Methodsmentioning
confidence: 99%
“…Cells from 3 wells were counted at each time point, and the experiment was repeated 6 times. For pathway exploration, cells were preincubated with PI3K inhibitor (LY294002; 20 μ M; Selleckchem) for 2 h [21] and then incubated with MSC-EXs miR-126 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the overexpression of miR-125a-5p resulted in a reduction of seizures and lessened hippocampal inflammation via the suppression of its target gene, calmodulindependent protein kinase IV (CAMK4) [139]. Pan et al showed that microvesicles carrying miR-125a-5p fostered the proliferation, migration, the ability to form tubes of transfected microvessel BECs, improved their apoptotic rate [141], while an earlier study discovered the role of this microRNA in protecting BECs from the injurious effects of oxidized low-density lipoproteins such as, senescence, decrease of nitric oxide (NO), and upsurge of reactive oxygen species (ROS) [142]. It is therefore likely that this microRNA plays a distinctive role in CCM patients presenting with epilepsy, or it could hypothetically act as a biomarker in identifying the cases liable to develop CCM-stimulated seizures.…”
Section: Mir-125amentioning
confidence: 99%